2013
DOI: 10.3389/fphys.2013.00246
|View full text |Cite
|
Sign up to set email alerts
|

Overview on how oncogenic Kras promotes pancreatic carcinogenesis by inducing low intracellular ROS levels

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a devastating disease without clearly known disease causes. Recent epidemiological and animal studies suggest that the supplementation of dietary antioxidants (e.g., vitamins C and E) decreases cancer risk, implying that increased reactive oxygen species (ROS) may play a role in pancreatic carcinogenesis. However, oncogenic Kras mutations (e.g., KrasG12D), which are present in more than 90% of PDAC, have been proven to foster low intracellular ROS levels. Here, oncoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 56 publications
3
41
0
1
Order By: Relevance
“…Nrf2 induces expression of many cytoprotective proteins responsible for maintaining cellular redox stability. Recent study also showed that nuclear Nrf2 expression play an important role in ROS detoxification during pancreatic carcinogenesis (29), and is related to a poor survival in patients with pancreatic adenocarcinoma (30). Western blot analysis showed that the expression of Nrf2-targeting antioxidants such as SOD1, GPX, GST-Pi, GCLC, and GCLM, was increased following gemcitabine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 induces expression of many cytoprotective proteins responsible for maintaining cellular redox stability. Recent study also showed that nuclear Nrf2 expression play an important role in ROS detoxification during pancreatic carcinogenesis (29), and is related to a poor survival in patients with pancreatic adenocarcinoma (30). Western blot analysis showed that the expression of Nrf2-targeting antioxidants such as SOD1, GPX, GST-Pi, GCLC, and GCLM, was increased following gemcitabine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Resulting damage from oxidative stress, if substantial, can lead to cell death unless adaptive processes are implemented that can withstand the harmful effects. ROS comprises oxygen-derived molecules and free radicals which can arise during normal metabolism (Turrens, 2003), and also during cell proliferation or abnormal and stressful events, such as endoplasmic reticulum (ER) stress or oncogenic transformation (Zhang and Kaufman, 2008;Logsdon and Ji, 2013;Kong et al, 2013). Moreover, exogenous toxic environmental agents, such as chemotherapy drugs and cigarette combustion products, may also induce free radicals (Hayes and McMahon, 2009;Ju et al, 2015).…”
Section: Redox Cellular Stressmentioning
confidence: 99%
“…The sustained Nrf2 signaling in AsPC-1 may be due to activating KRAS mutation [28]. Oncogenic KRAS is a key driver mutation in PDAC tumorigenesis [36] and is shown to render lower intracellular ROS levels by activating Nrf2 programs [37]. KRAS mutation is also essential in promoting glutaminolysis in PDAC to fuel anabolic processes in supporting cell growth [38, 39].…”
Section: Discussionmentioning
confidence: 99%